Shamba Shape Up: Using digital channels to deliver bundled agriculture, climate, and financial information services: IPSR Innovation Profile - Chilambe, Pedro Anglaze; Gichinga, Patricia; Girvetz, Evan Hartunian (2022)
Shamba shape is a farm makeover show which reaches over 8 million viewers in Kenya, and is now scalling up its reach to a show in Zambia and we would like to propose its scale up also to Uganda. The show will bring in new elements, providing seasonal forecasting to farmers with agro-advisory, reporting on FEWS-net early warning and agro-meteorological bulletins for access by smallholder farmers, through TV, Radio and the IShamba mobile app.